A reflection on learning crafts as a practice for self-development. Issue 2 (4th March 2017) - Nasseri, M.; Wilson, S.
Abstract: This paper represents a reflection on craft as a process that stimulates self-development. Central to this approach is the perception of craft, not as a means of production, but as an exercise of relating to the world. The paper suggests that through the dialogue between the mind, body and environment craft practitioners experience a particular form of connection with the world that reshapes their perceptual and conceptual understanding of it. Rather than following an ego-driven tendency to control, a craftsperson is exposed to modes of 'knowing' and 'being' that embrace the inherent uncertainty of a complex world. The learning experience of a novice (lead author) demonstrates such a course of development in this paper. In particular, the liminal space that needs to be created for the dialogue between the self and the non-self is explored. This personal narrative is woven together with the experience of craft masters within different social contexts and value systems (from traditional to modern to postmodern) and their views on the process of being and becoming a craftsperson.